KEBIJAKAN HUKUM PIDANA TERHADAP PEMALSUAN SURAT KETERANGAN NEGATIF COVID-19 - I Wayan Putu Sucana Aryana (Fakultas Hukum Universitas Ngurah Rai, 2020)
The criminal policy on COVID-19 negative health certificates stating conditions that are not true or falsified are very important in efforts to accelerate the response to the COVID-19 pandemic. In the context of counterfeiting COVID-19 negative statements, the intended criminal law policy is the policy in applying the law. The penalties policy in the falsification of COVID-19 negative letter of statements must see who is the legal subject who is the perpetrator. Perpetrators other than doctors are convicted under the provisions of Article 268 of the Indonesian Criminal Code, whereas if the perpetrators are doctors, they are convicted according to Article 267 of the Indonesian Criminal Code.